Austerity Without Consolidation: Fiscal policy and spending choices in Budget 2023 - Sachs, Michael; Amra, Rashaad; Madonko, Thokozile; Willcox, Owen (Southern Centre for Inequality Studies (SCIS), 2023)
Fiscal policy can play a crucial role in fostering growth and development by ensuring the sustainable delivery of essential public services. Managed effectively, government’s budget can help us build a common society and overcome the segregation and inequality of the past, without which sustained economic growth seems unlikely. It can also respond to temporary macroeconomic shocks to aggregate demand and livelihoods. South Africa however finds itself in a worsening fiscal impasse. There is continuous austerity, dating back more than a decade, but South Africa appears no closer to achieving fiscal consolidation. This position is steadily eroding the fiscal capabilities necessary for the state to realise the potential that fiscal action offers. Instead, the budget is increasingly becoming a drag on development.
Spending Choices 2023
Keywords: Austerity; Fiscal policy; Spending choices in Budget 2023; Public Economy